Biosynthesis of Antimicrobial Silver Nanoparticles against Gram-Negative and Gram-positive Bacteria by the Entophytic Fungus Aspergillus Fumigatus - Suleman Khan, Mahdi H. Alsugoor, Farkad Bantun, Saad Alghamdi, Naif Alsuhaymi, Anas S.Dablool, Zain Alhindi, Muhammad Salman, Komal Aman (Pakistan Journal of Medical & Health Sciences, 2022)
Multi drug resistance is increasing day by day due to misuse of antibiotics. Several potent metabolites are produced by fungi. Synthesis of silver nanoparticle (AgNPs) Due to its simple, harmless, time-saving, and cost-effective characteristics, it has acquired great popularity in recent years. A variety of analytical techniques were used to synthesize AgNPs from Aspergillus fumigatus extracts, including X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and Transmission Electron Microscopy (TEM). The effect of synthesis AgNPs and crude extract noted against different bacterial pathogens. Maximum antibacterial activity were noticed against tested bacteria by both fungal crude extract and (AgNPs) Maximum antibacterial activity of Ethyl acetate crude extract at 50µl concentration (12mg/1ml DMSO) showed (15mm) zone of inhibition against E.coli. While minimum antibacterial activity of Ethyl crude extract at 50µl concentration was observed against S.typhi (12mm). Highest antibacterial activity of Ethyl acetate crude extract at 100µl was noted against E.coli which showed (20mm) zone of inhibition. While (17mm) zone of inhibition was observed against S.typhi at 100µl concentration Ethyl acetate crude extract and AgNPs (25mm) zone of inhibition was observed against E.coli at 100µl concentration Ethyl acetate crude extract and AgNPs respectively. During UV-visible spectroscopy, surface Plasmon Resonance (SPR) was observed at 432 nm, which confirmed the synthesis of AgNPs. The SEM micrograph demonstrated the spherical shape of AgNPs. The results of FTIR research revealed that phenolic, carboxyl, and hydroxyl groups played a crucial role in the reduction of Ag+ ions into AgNPs, while amide linkage and amino acids stabilized AgNPs. AgNPs synthesized were XRD peaks that revealed phase purity, size, internal crystalline structure, and nature. In the pharmaceutical and medical fields, AgNPs synthesized from Aspergillus fumigatus extract could be of great importance. While, the combination of AgNPs and crude extract Aspergillus fumigatus enhances their antimicrobial effect which increase their importance in future studies